2019
DOI: 10.3390/agronomy9050262
|View full text |Cite
|
Sign up to set email alerts
|

Urea Addition Promotes the Metabolism and Utilization of Nitrogen in Cucumber

Abstract: Nitrogen (N) forms include ammonium [NH4+-N], nitrate [NO3−-N], and urea [CO(NH2)2]. Urea is the most common nitrogen fertilizer in agriculture due to its inexpensive price and high N content. Although the reciprocal influence between NO3−-N and NH4+-N is well known, CO(NH2)2 interactions with these inorganic N forms have been poorly studied. We studied the effects of different nitrogen forms with equal nitrogen on dry matter, yield, enzyme activity, and gene expression levels in cucumber. NO3−-N treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Moreover, different physiological responses of plants to an equal N‐amount supply of urea and NO 3 − or NH 4 + have been observed depending on plant species. In wheat, tomato and cucumber, the uptake of urea, total N, biomass and enzyme activities for N‐assimilation are significantly increased in plants fed with urea combined with NO 3 − and/or NH 4 + (Mérigout et al ., 2008b; Lupini et al ., 2017; Ma et al ., 2019), whereas in Arabidopsis , oilseed rape and maize the coinstantaneous supply of urea and NO 3 − reduces the acquisition of urea and the total N by the plants (Mérigout et al ., 2008a; Arkoun et al ., 2012; Zanin et al ., 2015). Nevertheless, the effect of urea as a N‐nutritional source on plant growth and development seems to be intricate and elusive, and the related mechanism(s) is worth to be extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, different physiological responses of plants to an equal N‐amount supply of urea and NO 3 − or NH 4 + have been observed depending on plant species. In wheat, tomato and cucumber, the uptake of urea, total N, biomass and enzyme activities for N‐assimilation are significantly increased in plants fed with urea combined with NO 3 − and/or NH 4 + (Mérigout et al ., 2008b; Lupini et al ., 2017; Ma et al ., 2019), whereas in Arabidopsis , oilseed rape and maize the coinstantaneous supply of urea and NO 3 − reduces the acquisition of urea and the total N by the plants (Mérigout et al ., 2008a; Arkoun et al ., 2012; Zanin et al ., 2015). Nevertheless, the effect of urea as a N‐nutritional source on plant growth and development seems to be intricate and elusive, and the related mechanism(s) is worth to be extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…To date, molecular physiological studies have demonstrated that AMTs and DUR3 homologs are crucial genetic components required respectively for high-affinity uptake/transport of NH 4 + and urea in plants (Wang et al, 2012;Liu et al, 2015;Liu and Wirén, 2017). Metabolic profiling of amino acids in shoots of Arabidopsis supplied with 15 N-urea and -NH 4 + to roots reveals that urea and NH 4 + share similar assimilation processes in cells (Mérigout et al, 2008a (Mérigout et al, 2008b;Lupini et al, 2017;Ma et al, 2019), whereas in Arabidopsis, oilseed rape and maize the coinstantaneous supply of urea and NO 3 − reduces the acquisition of urea and the total N by the plants (Mérigout et al, 2008a;Arkoun et al, 2012;Zanin et al, 2015). Nevertheless, the effect of urea as a N-nutritional source on plant growth and development seems to be intricate and elusive, and the related mechanism(s) is worth to be extensively investigated.…”
mentioning
confidence: 99%
“…The values of different forms of nitrogen in the inorganic treatment group were increased compared with the organic and control groups. This may be a result of the high nitrogen content from the addition of urea, which dissolves in water and is rapidly converted to ammonia [ 43 ]. A higher total phosphorus content occurred in the organic treatment group, which may be due to organic fertilizer decomposition by bacteria which releases both forms of phosphorus [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scientific investigations that recommend nitrogen fertilization in protected cultures are generalized and only mention the recommendation tables of total N concentrations in nutrient solutions. In general, studies only refer to nitrate (NO3 -) concentrations, not including the ammoniacal form (NH4 + ) for the cultivation of cucurbits and not addressing their ideal or toxic concentrations for plants (Ma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In plants considered sensitive to NH4 + , such as cucurbits, the use of ammonium, even at moderate concentrations, can impair development and may lead to plant death due to biochemical, physiological, and nutritional changes (Ma et al, 2019). Thus, researches that study the ideal concentrations of this nitrogen source are increasingly necessary in order to adjust the crop fertilization program of hydroponic or fertigated systems.…”
Section: Introductionmentioning
confidence: 99%